Waiting times for outpatient treatment in Germany: New experimental evidence from primary data - Nils Heinrich; Ansgar Wübker; Christiane Wuckel (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
Long waiting lines are a common feature and a major concern in many public health care delivery systems. The waiting lines are often characterized as inefficient, because they are a burden to patients without generating any gains for providers. There is an ongoing debate in Germany regarding the preferential treatment given to private health insurance (PHI) holders while statutory health insurance (SHI) holders face continuously increasing waiting times. In order to tackle this problem in the outpatient sector, in 2015 Germany introduced a reform that was aimed at providing SHI holders with appointments within an acceptable time frame. We exploited longitudinal experimental data to examine waiting times for six elective outpatient treatments in Germany and assessed the reform's impact on this issue. We found a sizeable difference in waiting times favoring private patients. For SHI holders, waiting times remained stable over time (27.5 days in 2014; 30.7 days in 2016; ? 3.2 days, p-value = 0.889), while PHI holders experienced a significant improvement (13.5 days in 2014; 7.8 days in 2016; ? 5.7 days, p-value = 0.002). The results indicate that there is an unequal access to elective outpatient treatment depending on the patient's insurance status. Our conclusion is that, the reform did not repair the existing inequalities. The gap has rather widened. – – Lange Wartezeiten sind eine große Herausforderung in vielen öffentlichen Gesundheitssystemen. Sie gelten als ineffizient, da sie eine zusätzliche Belastung für Patienten darstellen, ohne dass der Leistungserbringer, hier der Arzt, einen ausgleichenden Nutzen daraus zieht. In Deutschland wird aktuell diskutiert, ob Versicherte der Privaten Krankenversicherung (PKV) bei der Terminvergabe bevorzugt werden, während Versicherte der Gesetzlichen Krankenversicherung (GKV) stetig wachsenden Wartezeiten ausgesetzt sind. Um diesem Problem im ambulanten Sektor entgegenzuwirken wurde in Deutschland im Jahr 2015 eine Reform verabschiedet, die darauf abzielt, GKV-Patienten einen Arzttermin innerhalb eines akzeptablen Zeitrahmens zu vermitteln. Anhand der in einer Längsschnittstudie erhobenen Daten haben wir die Wartezeiten für sechs elektive, ambulante Behandlungen in Deutschland betrachtet sowie den Einfluss der Reform auf das Problem untersucht. Wir haben einen beträchtlichen Unterschied der Wartezeiten zugunsten der privatversicherten Patienten beobachtet. Für GKV-Patienten blieben die Wartezeiten über die Zeit konstant (27,5 Tage in 2014, 30,7 Tage in 2016, ? 3,2 Tage, p-Wert = 0.889), während PKV-Patienten einen signifikanten Rückgang erfahren haben (13,5 Tage in 2014; 7,8 Tage in 2016; ? 5,7 Tage, p-Wert = 0.002). Die Ergebnisse zeigen, dass es einen ungleichen Zugang zu elektiven, ambulanten Behandlungen gibt, welcher vom Versicherungsstatus des Patienten abhängig ist. Unser Fazit ist, dass die Reform diese Ungleichheiten nicht beseitigt hat. Die Ungleichheit hat sich eher vergrößert.
Keywords: I10; I11; I18; 330; Waiting times; outpatient care; Germany; public health insurance; private health insurance